Table 1_Endangered Galápagos sea lions and fur seals under the siege of lethal avian flu: a cautionary note on emerging infectious viruses in endemic pinnipeds of the Galápagos Islands.docx - Juan José Alava; Ana Tirapé; Judith Denkinger; Paola Calle; Patricia Rosero R.; Sandie Salazar; Patricia A. Fair; Stephen Raverty (2024)
The full text of this article can be freely accessed on the publisher's website.